STRATEGI PENGEMBANGAN INTERAKSI SOSIAL ANAK USIA DINI (5-6 TAHUN) MELALUI TEKNIK ROLE PLAYING - Karin Ariska; Rahmawati Rahmawati (Jurnal Panrita, 2024)
At school, some children still encounter difficulties in interacting with others around them. This can be observed through behaviors such as preferring solitude, unwillingness to share, reluctance to cooperate, and displaying expressions of anger, sadness, and fear while at school. This study aims to describe the social interactions of early childhood children at TK Assalam 1 Sukarame, Bandar Lampung. The research method used is descriptive qualitative. The subjects in this study were classroom teachers and children aged 5-6 years in group B1. Data collection tools included observation results, interviews, and documentation. The data collected were analyzed through data reduction, display, and drawing conclusions. The results of this study indicate that teachers use six methods to develop social interaction through role-playing techniques: 1) Teachers narrate the storyline to be played based on the theme, 2) Teachers prepare the props to be used, 3) Teachers demonstrate the roles to be played, 4) Teachers provide opportunities for children to take on roles, 5) Teachers remind children of their play experiences, and 6) Teachers guide children in tidying up the equipment.